Robust control on saturated Markov jump systems with missing information - Shi, Peng; Yin, Yanyan; Liu, Fei; Zhang, Jianhua (Information sciences, 2014)
In this paper, a robust H∞ controller is designed for saturated Markov jump systems with uncertainties and time varying transition probabilities. The time-varying transition probability uncertainty is described as a polytope set. Stochastic stability is analyzed for the underlying systems by Lyapunov function approach and a sufficient condition is derived to design controllers such that the resulting closed-loop system is stochastically stable and a prescribed H∞ performance is also achieved. Furthermore, the attraction domain of this Markov jump system is estimated and evaluated. A simulation example is given to show the effectiveness of the developed techniques.